1994
DOI: 10.1002/pola.1994.080320815
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐transfer catalytic activity of soluble polystyrenes containing crown ether moieties and hydroxyl groups adjacent to the macrorings

Abstract: Soluble polystyrenes with crown ether structures and hydroxyl groups adjacent to the macrorings were prepared by the reaction of epoxide‐containing polystyrenes with monoaza‐15‐crown‐5 or monoaza‐18‐crown‐6. Rate of formation of the polymer‐bound alkali cation‐crown alkoxide ion pair from the soluble polystyrenes and aqueous NaOH or KOH depended on the loading of crown ether and hydroxyl units and on the size of the macroring. The elimination of HCl from less reactive 2‐chloroethylbenzene with aqueous NaOH or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…128,151,164 Various classes of crown ethers attached to polymers have been of interest due to their selective ionic binding of complexes with metal cations. [190][191][192][193][194] π-Conjugated polymers such as polypyrroles 192,195 and polythiophenes 196,197 functionalized with crown ether were extensively investigated to explore the ion-selective electrodes and sensory materials. The polymerization of 4′,4′-ethynylbenzo-1,5-crown-5 was carried out using the rhodium complex catalyst (bicyclo[2.2.1]hepta-2,5-diene)rhodium(I) chloride dimer, [Rh(bhd)-Cl 2 ], 197,198 to give a maximum 55% yield of a polymer.…”
Section: A Poly(16-heptadiyne) and Its Homologuesmentioning
confidence: 99%
“…128,151,164 Various classes of crown ethers attached to polymers have been of interest due to their selective ionic binding of complexes with metal cations. [190][191][192][193][194] π-Conjugated polymers such as polypyrroles 192,195 and polythiophenes 196,197 functionalized with crown ether were extensively investigated to explore the ion-selective electrodes and sensory materials. The polymerization of 4′,4′-ethynylbenzo-1,5-crown-5 was carried out using the rhodium complex catalyst (bicyclo[2.2.1]hepta-2,5-diene)rhodium(I) chloride dimer, [Rh(bhd)-Cl 2 ], 197,198 to give a maximum 55% yield of a polymer.…”
Section: A Poly(16-heptadiyne) and Its Homologuesmentioning
confidence: 99%
“…This seems a little surprising at first bearing in mind the synthetic utility of sulphonium salts as building blocks, but the latter of course are alkyl or alkylaryl species. The second development is from Tomoi et al [102]. They have shown that monoaza-crowns can be attached conveniently to polystyrene resins carrying epoxide groups via facile ring opening of the latter.…”
Section: Phase Transfer Catalystsmentioning
confidence: 98%
“…[1][2][3] It is also well known that insoluble polystyrene beads carrying pendant crown ether group as well as pendant quaternary ammonium or phosphonium salts can be used as phase transfer catalyst in liquid-solid-liquid heterogeneous organic synthesis. 4,5 It has been suggested that polystyrene containing crown ethers and mono azacrown ethers were used as phase-transfer catalysts for dehydrohalogenation, addition and substitution reaction and other organic reaction. 6 The major advantages of the polymer-supported phase transfer catalyst [7][8][9][10] are: (1) ease of separation from reaction mixture by filtration; and (2) recycling of the catalyst.…”
mentioning
confidence: 99%